'Do not expect me to stay quiet': Challenges in managing a historical strategic resource. Issue 12 (December 2018) - Cailluet, Ludovic; Gorge, Hélène; Özçağlar-Toulouse, Nil
In this paper we explore how a historical strategic resource (HSR) could be used by an organization. We propose that within an organization, HSR is both an asset and an arena for power struggle. Our contributions stand at several levels at the crossroads of strategic management and organizational studies. First, we show the importance of various stakeholders in constructing a HSR. Second, we highlight its complexity due to its embeddedness with history. The fact that a HSR could be akin to a public good implies that its rents are difficult to control for organizations. To uncover what is meant by a historical resource, we first present a review of the resource-based theory and the uses of the past in organizations from the perspective of organization theory and organizational history. We then present our fieldwork, which focuses on Emmaus, a major charity organization in France, and its founder, Abbé Pierre. Based on a historical study covering the period 1949 to 2017 drawing on the organization's archives, online publications and data from the French national audiovisual archives, we identify visual and rhetorical elements that constitute Abbé Pierre and his past as HSR for the Emmaus organization. Eventually, our paper contributes to the literature by offering a four-dimensional management framework for HSR with appropriation, ownership, maintenance and distancing.